Schizophrenia Of the Main Character In Fear Of Rain Movie Directed By Castille Landon - Nijam, Infrida (EDUJ : English Education Journal, 2023)
Literature is something that cannot be separated from people's lives, and films are one of the most popular forms of literary works today. Mental health is an important focus in everyone's life, to maintain and maintain sanity for a better life. This study discusses mental health problems, namely schizophrenia, with films as research objects. The purpose of this study was to find out the early symptoms of schizophrenia, the impact of schizophrenia, and the role of parents in responding to children with schizophrenia. This research uses descriptive qualitative method where the data collected is in the form of words, pictures and not numbers. Schizophrenia has two types of initial symptoms, namely positive symptoms and negative symptoms. In "FEAR OF RAIN" movie, the writer found that the character Rain (1). experiences positive symptoms, such as hallucinations and delusions. (2). The impact of schizophrenia makes it difficult for Rain to adapt to her family, friends and environment, because relapse can pose serious risks such. (3). In the film, the role of parents is very important like Rain parent’s who always accompany and support Rain in every difficult time. This shows how important the role of parents is in the condition of children with schizophrenia.The conclusion is that in  Fear of Rain movie the main character experiences early symptoms in the form of hallucinations and delusions that cause Rain to experience excessive anxiety and aggressive behavior.